Clinical Studies On Chemical Immobilization Of Stray Bulls For Capture And Rehabilitation: Part I - Joshi, D.O.; Tank, P.H.; Dhami, M.A.; Maradia, M.G.; Dhami , A.J.; Patel , P.R. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A clinical study on chemical immobilization with blow dart was conducted on 40 stray bulls. Xylazine was administered intramuscularly @ 0.1 mg/kg b.wt. Group I-A, n=10, and @ 0.2 mg/kg b.wt. Group I-B, n=10, while Xylazine and Ketamine (XK) mixture was administered @ 1.0 ml/bull 55.55 mg Xylazine and 44.44 mg Ketamine, Group II-A, n=10 younger and lighter bulls and @ 1.5 ml/ bull 83.32 mg Xylazine and 66.66 mg Ketamine, Group II-B, n=10 adult and heavier bulls. Group I-A bulls showed complications like increased chase time, rapid breathing, tachycardia, either hyperthermia or hypothermia and hypersalivation. Despite completely sedated, Group I-B bulls could move or kick, produced prolonged sedation time, unreliable immobilizations, rumen stasis and tympany. XK mixture (Group II) produced marked synergistic effect, reduced dosages, thus minimizing the antagonistic reactions and other hazards involved with, faster and smoother induction and sedation. Results of the present study indicated that Xylazine @ 0.2 mg/kg b.wt. or XK mixture @ 1.0-1.5 ml per bull for chemical immobilization at an approximately 4 meters darting distance is effective for its uneventful capture.